Role of aliovalent cation doping in the activity of nanocrystalline CdS for visible-light-driven H-2 production from water - Korake, Prakash V.; Achary, Srungarpu N.; Gupta, Narendra M. (International Journal of Hydrogen Energy, 2015)
This study was aimed at discerning the enhancement in the visible-light-driven water splitting activity of nanocrystalline CdS photocatalysts because of their doping with a small amount of an aliovalent cation (Ag+ or Cr3+). The CdS/Cr-x (x = 0-2.3 wt%) and CdS/Ag-x (x = 0-1.5 wt%) samples, which were synthesized using a one-step hydrothermal method, were characterized systematically for their crystallographic, morphological, interfacial, and photo-physical properties. The Rietveld refinement of the powder X-ray diffraction data enabled us to quantify the doping-effect on the phase composition and lattice parameters. As compared to pure CdS, the samples containing similar to 0.2 wt% of Cr or Ag showed two or tenfold enhancement in the rate of H-2 evolution from water, respectively, when sulfide-sulfite ions were used as sacrificial electron donors. This pyramidal trend, i.e. maximum activity for a specific impurity content, which decreased on decreasing as well as increasing the amount of doping, did not occur owing to the presence of a secondary-phase metal sulfide or a dispersed metal cocatalyst. Our study revealed that instead of the widely advocated mechanism involving inter-semiconductor or semiconductor-to-metal electron transfer steps, the doping-modified photoactivity of CdS was governed by certain bulk and surface properties such as the cation-dependent particle nucleation, dominance of hex-CdS facets, and structural defects. Additionally, impurity-induced sub-bandgap charge-trapping states also contributed to the overall quantum efficiency. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.